THE EFFECTS OF NEBIVOLOL THERAPY ON QT DISPERSION IN CONGESTIVE HEART FAILURE - Kutlu, M.; Akbulut, M.; Ozbay, Y.; Bilen, M.; Cekici, Y.; Kobat, M. (Elsevier Ireland Ltd, 2008)
[Abstract Not Available]